Cynics and Skeptics: Evaluating the Credibility of Mainstream and Citizen Journalism. (September 2014) - Carr, D. Jasun; Barnidge, Matthew; Lee, Byung Gu; Tsang, Stephanie Jean
With the increase in citizen-generated news, the need to understand how individual predispositions interact with news sources to influence perceptions of news credibility becomes increasingly important. Using a web-based experiment, this study examines the influences individual predispositions toward the media and politics have on perceived credibility of mainstream and citizen journalism. Analyzing data drawn from a representative sample of the U.S. adult population, results indicate that media skepticism and political cynicism interact, such that cynics and skeptics perceive citizen journalism as more credible, while non-cynics and non-skeptics think mainstream journalism is more credible.